The impact of physical training and special preparation on the development of strength and endurance in adolescent judokas - Kryvytskyi, Artur (Педагогічна Академія: наукові записки, 2025)
The relevance of the study is determined by the need to reconsider the system of training young athletes in the context of modern educational and social challenges. Judo is viewed not only as a sport but also as a tool for cultivating discipline, promoting a healthy lifestyle, and integrating children into the social environment. At the same time, the development of strength and endurance during adolescence remains a key factor in shaping a competitive athlete. The purpose of the article is to clarify the role of physical loads and special preparation not only as a means of developing motor qualities but also as a factor in harmonizing the educational process and socialization of adolescent judokas. The research methodology employed an interdisciplinary approach, combining the analysis of pedagogical concepts, the study of sports school practices, and the generalization of experience in integrating sports programs into the system of extracurricular education. The studyʼs results demonstrated that physical training, when structured in combination with specialized elements, has a positive effect not only on physical performance growth but also on the discipline, responsibility, and communication skills of adolescents. Such integration reduces dropout rates from sports sections, increases interest in systematic training, and fosters long-term motivation for sports. The scientific novelty lies in interpreting the development of strength and endurance not only as a biomechanical process but as a complex phenomenon that influences the educational and social trajectory of young athletes. It broadens the traditional understanding of the training process by including educational and communicative aspects. The conclusions confirmed that the harmonious combination of physical training and special preparation contributes not only to athletic performance but also to social adaptation and personal development of adolescents. Thus, judo performs two functions ˗ sporting and educational ˗ making it a unique tool for multidimensional development. Prospects for further research involve studying the effectiveness of integrating sports programs into school education, analyzing the impact of physical training on the formation of resilience, and examining the social capital generated through adolescentsʼ engagement in systematic judo practice.